Pemanfaatan Algoritma Porter Stemmer Untuk Bahasa Indonesia Dalam Proses Klasifikasi Jenis Buku - Indriyono, Bonifacius Vicky; Utami, Ema; Sunyoto, Andi (Universitas Atma Jaya Yogyakarta, 2015)
Abstract. Stemming is the process of mapping and decomposition of various forms (variants) of a word to essentially find the root word. This process is also referred to as the conflation. Stemming process has been widely used in the activities of the information retrieval (search information) to improve the quality of the information obtained. Stemming works by employing words taken froma dictionary and the usage of the basic rules of affixes. Porter stemmer for Indonesian or commonly referred as Tala stemmer uses the rules of basic analysis to find the root of a word. Tala Stemmer does not use a dictionary in the process. Instead, it uses a rule-based algorithm. In this study, the principal issue raised is how to make the process of classification/determination of the book/library materials in a library with a fast and effective manner in order to minimize error in determining the type of books. The solution is to utilize the method used by the porter stemmer for stemming Indonesian.Keywords: Stemming, Information Retrieval, Porter Stemmer, ClassificationÂ Abstrak. Stemming adalah proses pemetaan dan penguraian berbagai bentuk (variants) dari suatu kata menjadi bentuk kata dasarnya. Proses ini juga disebut sebagai conflation. Proses stemming secara luas sudah digunakan di dalam kegiatan Information retrieval (pencarian informasi) untuk meningkatkan kualitas informasi yang didapatkan. Cara kerja stemming dapat dilakukan dengan menggunakan kamus kata dasar maupun menggunakan aturan-aturan imbuhan. Porter stemmer untuk Bahasa Indonesia atau yang biasa disebut dengan stemmer Tala menggunakan rule base analisis untuk mencari root sebuah kata. Stemmer Tala tidak menggunakan kamus dalam proses, melainkan menggunakan algoritma berbasis aturan. Dalam penelitian ini, pokok permasalahan yang diangkat adalah bagaimana melakukan proses klasifikasi/penentuan jenis buku/bahan pustaka dalam sebuah perpustakaan dengan cara yang cepat dan efektif sehingga dapat meminimalisir kesalahan penentuan jenis buku. Solusi yang dipergunakan adalah dengan memanfaatkan metode stemming dengan porter stemmer untuk bahasa Indonesia.Kata Kunci: Stemming, Information Retrieval, Porter Stemmer, Klasifikasi